Rivers under stress: geochemical changes along a rural–urban gradient during extreme hydrological events (Greve River, Italy) - M. Ferrari; R. Biagi; S. Venturi; F. Frezzi; F. Tassi (Environmental Geochemistry and Health, 2026)
Rivers are increasingly exposed to combined anthropogenic and climate-driven pressures, particularly along rural-to-urban gradients where land use, population density, and contaminant sources progressively intensify downstream. In parallel, prolonged droughts followed by intense rainfall events are becoming more frequent, potentially enhancing contaminant accumulation during dry periods and their rapid mobilization during subsequent first-flush events. However, the interactions between these hydrological extremes and spatial anthropogenic gradients in controlling river geochemistry remain insufficiently understood. This study investigates the spatial and seasonal evolution of river chemistry along the Greve River (Tuscany, Italy), a tributary of the Arno River, characterized by a marked rural-to-urban transition, during the exceptional 2022 European drought and subsequent heavy rainfall event. Six sampling campaigns were conducted between May and October 2022, combining high-resolution spatial monitoring with geochemical and isotopic tracers, including total dissolved solids (TDS), nutrients, and trace elements. The results reveal a progressive downstream enrichment in anthropogenic tracers (e.g., NO 3 − and K + , up to 9 mg/L and 6.6 mg/L, respectively) and pronounced evaporative isotope enrichment during the driest months (slope of the evaporation line ~ 4), indicating strong hydrological stress conditions. The first intense rainfall event triggered rapid remobilization of accumulated material and heterogeneous contaminant transport dynamics. Elevated nutrient concentrations (e.g., NH 4 + , up to 1.4 mg/L) in downstream sectors further reflect the combined influence of hydrological stress and urban inputs. These findings demonstrate how climate-driven hydrological extremes can amplify contaminant mobilization along urbanized river continuums. The integration of isotopic and geochemical tracers provides a transferable framework for assessing water-quality vulnerability in river basins increasingly exposed to hydroclimatic instability.

A novel integrated strategy for air quality monitoring in volcanic-hydrothermal, wetland, urban and industrial areas - R. Biagi; A. Randazzo; S. Venturi; F. Capecchiacci; O. Vaselli; F. Tassi (Atmospheric Environment, 2025)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Traditional and low-cost technical approaches for investigating greenhouse gases and particulate matter distribution along an urban-to-rural transect (Greve River Basin, Central Italy) - M. Ferrari; R. Biagi; S. Venturi; F. Frezzi; F. Tassi (Environmental Geochemistry and Health, 2025)
Human activities, largely tied to fossil fuels and intensive agriculture, emit massive amounts of climate-altering species and harmful pollutants into the atmosphere that affect soil, ecosystems, and water. Air quality monitoring is crucial to minimize harmful effects and protect human and environmental health. The Greve River basin (Tuscany, central Italy) represents an excellent example of an ecosystem affected by various anthropogenic air contaminants. The upstream areas are predominantly rural, while the downstream zones are characterized by urban and industrial development. Air pollutants throughout the basin were measured adopting two strategies: (i) fixed monitoring at five sites using multiparametric stations equipped with low-cost sensors for CO 2 , CH 4 , and PM 2.5 concentrations; (ii) measurements along a transect using a mobile monitoring station equipped with a Picarro G2201- i analyzer for the determination of CO 2 and CH 4 concentrations and 13 C/ 12 C values of the two gases. Results revealed relatively high CO 2 and CH 4 concentrations downstream, mainly due to vehicular traffic based on the isotopic signature. The temporal and spatial distribution of the contaminants mirrored the evolution of the Planetary Boundary Layer, with peak concentrations in the early morning due to stable atmospheric conditions, and contaminant dilution due to air turbulence during the daytime. Particulate (PM 2.5 ) distribution showed a trend similar to gaseous pollutants, being strongly dependent on wind speed and rainfall events. The high spatiotemporal resolution of data acquisition provided by the low-cost stations for air quality measurements represents an important advance for developing monitoring strategies, complementing the traditional instrumentation commonly used by agencies.

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

−295 T-to-C promoter region IL-16 gene polymorphism is associated with Whipple’s disease - F. Biagi; A. Schiepatti; C. Badulli; I. Sbarsi; L. Trotta; G. E. Feurle; C. Müller; V. Moos; T. Schneider; T. Marth; M. De Amici; M. Martinetti; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Polymorphisms in VEGFA gene affect the antihypertensive responses to enalapril - G. H. Oliveira-Paula; R. Lacchini; V. Fontana; P. S. Silva; C. Biagi; Jose E. Tanus-Santos (European Journal of Clinical Pharmacology, 2015)

Prevalence of Whipple's disease in north-western Italy - F. Biagi; D. Balduzzi; P. Delvino; A. Schiepatti; C. Klersy; G. R. Corazza (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Comparative safety profiles of intravitreal bevacizumab, ranibizumab and pegaptanib: the analysis of the WHO database of adverse drug reactions - C. Biagi; V. Conti; N. Montanaro; M. Melis; E. Buccellato; M. Donati; A. Covezzoli; R. Amato; L. Pazzi; M. Venegoni; A. Vaccheri; D. Motola (European Journal of Clinical Pharmacology, 2014)

eNOS and BDKRB2 genotypes affect the antihypertensive responses to enalapril - P. S. Silva; V. Fontana; M. R. Luizon; R. Lacchini; W. A. Silva; C. Biagi; J. E. Tanus-Santos (European Journal of Clinical Pharmacology, 2013)

Cytokine genetic profile in Whipple’s disease - F. Biagi; C. Badulli; G. E. Feurle; C. Müller; V. Moos; T. Schneider; T. Marth; J. Mytilineos; F. Garlaschelli; A. Marchese; L. Trotta; P. I. Bianchi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Relative Growth and Sexual Maturity of the Hermit Crab Paguristes erythrops (Anomura, Diogenidae) from South Atlantic - R. Biagi; F.L.M. Mantelatto (Hydrobiologia, 2006)

Veterinary Case History: Forensic and Medical Legal Aspects - G. Signorini; G. Biagi; E. Luchetti; G. Cardini; R. Bernocchi (Veterinary Research Communications, 2004)